Rekontruksi Asas Perbuatan Melawan Hukum (Onrechtmatigedaad) Dalam Gugatan Sengketa Konsumen - Tanaya, Velliana (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
In a dispute over consumer protection, the plaintiff in this case is that consumers do not necessarily use the basic claim (posita) with the construction of Tort, but need to be reviewed again is there any legal relationship between consumers and business actors. If there is any relationship between the consumer and an entrepreneur based on contract thus the claim is based on breach of contract and if the consumer complaint using the qualification of tort, then the contractual relationship is not required. It is necessary to reconstruct the lawsuit to avoid an obscuur libel lawsuit which will end up to be niet ontvantkelijkverklaard.